EFFECTS OF PHYTASE SUPPLEMENTATION ON PRECAECAL DIGESTIBILITY OF PHOSPHORUS AND CRUDE PROTEIN OF SESAME SEED MEAL IN BROILERS (2013)
Sesame Seed Meal (SSM) is rich in phosphorus and Crude Protein (CP). However, these nutrients are bound by phytate, resulting in poor utilisation, and excretion of phosphorus and CP into the environment. The improvement of phosphorus and CP digestibility by the inclusion of phytase in feed can reduce their levels in poultry excreta. Information on supplementation of phytase to improve its phosphorus and CP digestibility is inadequately documented. The effects of phytase supplementation on Preceacal Digestibility (PD) of phosphorus and CP in broilers were therefore investigated. Two hundred and sixteen 1-day old broilers were randomly allotted to six dietary groups containing 0, 5, 10, 15, 20 and 25% SSM to replace soyabean meal with six replicates for each group. The broilers were fed for three weeks after which they were asphyxiated in CO2. Further, 210 one day old broilers were randomly allotted to seven diet groups containing 20, 25 and 30% SSM with or without phytase and a control (0%) with five replicates of each group, using completely randomized design, in 2 x 4 factorial arrangements. They were fed for three weeks after which samples of digesta were collected for PD of phosphorus, CP and Available P (AP). Another 210 one day old broilers were randomly allotted to seven diet groups containing 20, 25 and 30% SSM with or without phytase and a control (0%) with five replicates each, using completely randomized design, in 2 x 4 factorial arrangements. The birds were fed for six weeks, after which two birds from each replicate were sacrificed for tibia bone collection. Phosphorus and CP retention, Tibia Ash P (TAP, mg/g), Feed Intake (FI, g), Weight Gain (WG, g) and Feed Conversion Ratio (FCR) were recorded. Data were analysed using descriptive statistics, regression analysis and ANOVA at P>0.05. The PD (%) decreased from 42.2 to 29.6; 85.2 to 76.3 and 31.7 to 17.9 for phosphorus, CP and AP respectively for birds without phytase supplementation. Feed intake, WG, and FCR decreased significantly with increasing level of SSM. The PD (%) was between: 45.8 and 54.6; 85.1 to 91.8; 32.2 to 82.0% for phosphorus, CP and AP respectively for birds with phytase supplementation. The retention (between 64.4 and 85.2%); (between 27.6 and 51.8%) for P and CP respectively were significantly increased but there was no effect of phytase supplementation on TAP. The effects of interaction of phytase and SSM on PD of phosphorus and CP were significant. Phosphorus (0.0357) and CP (0.0545) retention were not significant. The FI ranged between 2963.0 and 3470.4, WG from 1576.2 to 1688.9 and were significantly improved by phytase supplementation. Interaction of phytase and SSM had significant effect on WG and FCR but not FI (0.0676). Replacing soybean meal with 15% sesame seed meal in broiler starter diet had no effect on performance while level of sesame seed meal above 15% reduced the performance, phosphorous and crude protein digestibility. With phytase supplementation sesame seed meal could be used up to 30% inclusion level.